Corn starch systems as carriers for yerba mate (Ilex paraguariensis) antioxidants: Effect of mineral addition - Schneider Teixeira, Aline (2015)
Corn starch is considered a good vehicle for delivering bioactive compounds such as supplements or health promoting additives. The ability of starch treated by high hydrostatic pressure (HHP) to bind and carry zinc and magnesium salts and natural antioxidants of yerba mate (Ilex paraguariensis) extracts was tested. A uniform distribution of the minerals on the surface of starch granules was observed by SEM-EDX and significantly higher amounts of minerals were loaded by HHP treated starches. Calorimetric analysis showed the effect of both HHP treatment and the active compounds addition, while crystal fraction was determined by X-ray diffraction, denoting the presence of minerals in the starch granule. It was found that the type of starch carrier did not affect total polyphenol loading. Besides, HPLC analysis showed that the relative composition of polyphenols from yerba mate extract was maintained. These results support the use of HHP treated corn starch as an alternative carrier for molecules of nutritional interest into food systems.